Isolation of Nontuberculous Mycobacteria in Southeast Asian and African Human Immunodeficiency Virus–infected Children With Suspected Tuberculosis. (28th January 2019) - Borand, Laurence; de Lauzanne, Agathe; Nguyen, Ngoc Lan; Cheng, Sokleaph; Pham, Thu Hang; Eyangoh, Sara; Ouedraogo, Abdoul-Salam; Ung, Vibol; Msellati, Philippe; Tejiokem, Mathurin; Nacro, Boubacar; Inghammar, Malin; et al.
Abstract: : We enrolled 427 human immunodeficiency virus–infected children (median age, 7.3 years), 59.2% severely immunodeficient, with suspected tuberculosis in Southeast Asian and African settings. Nontuberculous mycobacteria were isolated in 46 children (10.8%); 45.7% of isolates were Mycobacterium avium complex. Southeast Asian origin, age 5–9 years, and severe immunodeficiency were independently associated with nontuberculous mycobacteria isolation. Clinical Trials Registration: NCT01331811.